Motor and functional evaluation of patients with spastic paraplegia, optic atrophy, and neuropathy (SPOAN) Avaliação motora e funcional de pacientes com paraplegia espástica, atrofia óptica e neuropatia (SPOAN) - Zodja Graciani; Silvana Santos; Lucia Inês Macedo-Souza; Carlos Bandeira de Mello Monteiro; Maria Isabel Veras; Simone Amorim; Mayana Zatz; Fernando Kok (Arquivos de Neuro-Psiquiatria, 2010)
Spastic paraplegia, optic atrophy, and neuropathy (SPOAN) is an autosomal recessive complicated form of hereditary spastic paraplegia, which is clinically defined by congenital optic atrophy, infancy-onset progressive spastic paraplegia and peripheral neuropathy. In this study, which included 61 individuals (age 5-72 years, 42 females) affected by SPOAN, a comprehensive motor and functional evaluation was performed, using modified Barthel index, modified Ashworth scale, hand grip strength measured with a hydraulic dynamometer and two hereditary spastic paraplegia scales. Modified Barthel index, which evaluate several functional aspects, was more sensitive to disclose disease progression than the spastic paraplegia scales. Spasticity showed a bimodal distribution, with both grades 1 (minimum) and 4 (maximum). Hand grip strength showed a moderate inverse correlation with age. Combination of early onset spastic paraplegia and progressive polyneuropathy make SPOAN disability overwhelming. A paraplegia espástica, atrofia óptica e neuropatia (SPOAN) é uma forma complicada de paraplegia espástica de herança autossômica recessiva, caracterizada por atrofia óptica congênita, paraplegia espástica progressiva de início na infância e neuropatia periférica. Este estudo avaliou o desempenho motor e funcional de 61 indivíduos com SPOAN (5 a 72 anos), por meio do índice de Barthel modificado, a escala modificada de Ashworth, da avaliação da força de preensão das mãos com dinamômetro hidráulico de Jamar e escalas de paraplegia espástica hereditária. O índice de Barthel modificado, que investiga aspectos funcionais, mostrou-se mais sensível para avaliar a progressão da doença do que as escalas de paraplegia espástica. A espasticidade apresentou distribuição bimodal, com o grau 1 (mínimo) e 4 (máximo). A força de preensão mostrou correlação inversa moderada com a idade. A combinação de paraplegia espástica de início precoce com polineuropatia progressiva faz da SPOAN uma condição incapacitante.